THE PHYLLOSPHERE, INDOOR MICROBIOME AND HUMAN HEALTH - Favour O. Omeiza; Funmilola Ayeni (Global Journal of Public Health Medicine, 2020)
A healthy indoor environment is very vital as humans spend a greater percentage of their life within built environments. A healthy and quality environment is determined by the biodiversity of and features of the natural environment. The indoor environment just like every other environment possesses a unique community of microorganism which depends on the level of contact between the environment and natural sources. Plants are significant sources of microbial diversity in an environment. There is an interplay between the phyllosphere and the troposphere where the microorganisms released from the phyllosphere perform several beneficial effects consequently, improving human health. The indoor environment must however be enriched with natural sources of microbial release to enhance its biodiversity.  This paper therefore focuses on the phyllosphere as a natural source for enhancing indoor biodiversity, the interplay between the phyllosphere and its surrounding environment and its implication on human health.